2019
DOI: 10.1371/journal.ppat.1007589
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of cell-associated HTLV by plasmacytoid dendritic cells is regulated by dense β-galactoside glycosylation

Abstract: Human T Lymphotropic virus (HTLV) infection can persist in individuals resulting, at least in part, from viral escape of the innate immunity, including inhibition of type I interferon response in infected T-cells. Plasmacytoid dendritic cells (pDCs) are known to bypass viral escape by their robust type I interferon production. Here, we demonstrated that pDCs produce type I interferons upon physical cell contact with HTLV-infected cells, yet pDC activation inversely correlates with the ability of the HTLV-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 85 publications
(131 reference statements)
0
30
0
Order By: Relevance
“…What are the molecular mechanisms that regulate these pathways? Moreover, is viral biofilm present on different HTLV-1 infected cell lines similar in terms of composition, structure, and topography, given that these infected cells have different infectivity and ability to escape to innate sensing (Alais et al, 2015;Assil et al, 2019)? Viral biofilm has only been reported in in vitro models using HTLV-1-infected cell lines (Pais-Correia et al, 2010;Nakamura et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…What are the molecular mechanisms that regulate these pathways? Moreover, is viral biofilm present on different HTLV-1 infected cell lines similar in terms of composition, structure, and topography, given that these infected cells have different infectivity and ability to escape to innate sensing (Alais et al, 2015;Assil et al, 2019)? Viral biofilm has only been reported in in vitro models using HTLV-1-infected cell lines (Pais-Correia et al, 2010;Nakamura et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HTLV-1 entry in dendritic cells (DC) seems to rely on endocytosis, as inhibition of micropinocytosis or clathrindependent endocytosis completely abolished HTLV-1 capture by immature and mature DC, as well as subsequent productive infection of immature DC (Rizkallah et al, 2017). Besides, the role of Glut-1 in HTLV-1 viral biofilm entry in plasmacytoid dendritic cell (pDC) was confirmed, but not that of NRP-1 (Assil et al, 2019). In addition, while the same study also confirmed the role of Glut-1 in productive infection of T-cells after contact with HTLV-1 viral biofilm, it failed to demonstrate the need of NRP-1, suggesting that the proposed interaction of HTLV-1 envelop with NRP-1 as prerequisite before interaction with Glut-1 (Lambert et al, 2009) might not be mandatory when virions are embedded in biofilm and not cell-free.…”
Section: Biofilm Formation and Pathogen Spreadingmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphocytes are not the only cell type that HTLV-1 is able to infect. It has been reported that HTLV-1 can also infect monocytes/macrophages and dendritic cells [68][69][70][71][72][73][74][75][76], but their role in viral pathogenesis is not fully understood. In infected individuals, the majority of viral DNA is found in CD4 + and CD8 + T-cells.…”
Section: The P30 Protein Inhibits the Interferon Responsementioning
confidence: 99%